Concerns and confidences expressed by teaching staff about the shift of medical education to online mode in South India during the COVID 19 pandemic - Rafi, Aboobacker Mohammed; Varghese, Pulikkottil Raphael; Kuttichira, Praveenlal (Journal of Ideas in Health, 2020)
Background: Online education is prevalent in the country since the beginning of the 21st century. The outbreak of COVID-19, the government declared lockdown, and subsequent closing of institutions was unexpected, and it forced medical colleges to launch online programs for undergraduate courses. Due to the sudden shifting to online mode, most teaching staff members face the challenges of lacking online teaching experience, early preparation, or support from educational technology teams. This institution was in touch with the teachers and students through online mode, enquiring about their welfare and wellness. The present study focuses on concerns and confidences presented by the medical teaching staff on online medical education. Method: This study was conducted at Jubilee Mission Medical College & Research Institute, a medical college in central Kerala in south India. This institution conducted online classes for undergraduate (UG) medical students through Google classroom and YouTube platforms. There was 186 teaching staff from 21 departments involved in undergraduate (MBBS) teaching in this Institute. In this study, we collected information from the teaching staff about the online classes that they handled. A 27-point survey form was designed using a Google survey and mailed to them. The responses were collected in a week. The data collected was analyzed. Result: Fifty-one members responded. All responding teachers preferred regular classroom teaching due to the provision for better teacher-student interaction. However, one-third of respondents wanted the continuation of online classes, even after resuming classroom teaching. Out of 51 responses, 24 teachers graded the success of the programs more than 90%. The major suggestions received for further improvement of the program were that the departments provided their hardware and software, centralized online sessions for practical purposes, and collected regular feedback from students. Conclusion: The successes of our online teaching programs were limited to didactic teaching only. It could not replace the actual patient examination in a clinical setting, which involves communication skills and emotional relationships. This adversary must be converted into an opportunity to develop e-learning programs. This pandemic should open our eyes, so we learn from it and be better prepared for the future.